Lament ebook The faerie queen's deception. - Stiefvater, Maggie (Books of Faerie, 2010)
FROM THE AUTHOR OF THE NEW YORK TIMES BESTSELLING NOVEL SHIVER " Vibrant and potent, YA readers searching for faerie stories will be happy to find this accomplished debut novel." – Publishers Weekly (starred review) "This beautiful and out-of-the-ordinary debut novel, with its authentic depiction of Celtic Faerie lore and dangerous forbidden love in a contemporary American setting, will appeal to readers of Nancy Werlin's Impossible and Stephenie Meyer's Twilight series." – Booklist (starred review) "Part adventure, part fantasy, and wholly riveting love story, Lament will delight nearly all audiences with its skillful blend of magic and ordinary life." —KLIATT (starred review) Sixteen-year-old Deirdre Monaghan is a painfully shy but prodigiously gifted musician. She's about to find out she's also a cloverhand—one who can see faeries. Deirdre finds herself infatuated with a mysterious boy who enters her ordinary suburban life, seemingly out of thin air. Trouble is, the enigmatic and gorgeous Luke turns out to be a gallowglass—a soulless faerie assassin. An equally hunky—and equally dangerous—dark faerie soldier named Aodhan is also stalking Deirdre. Sworn enemies, Luke and Aodhan each have a deadly assignment from the Faerie Queen. Namely, kill Deirdre before her music captures the attention of the Fae and threatens the Queen's sovereignty. Caught in the crossfire with Deirdre is James, her wisecracking but loyal best friend. Deirdre had been wishing her life weren't so dull, but getting trapped in the middle of a centuries-old faerie war isn't exactly what she had in mind . . . Lament is a dark faerie fantasy that features authentic Celtic faerie lore, plus cover art and interior illustrations by acclaimed faerie artist Julia Jeffrey.